ANALYSING LOGISTIC MANAGEMENT OF CULINARY SMALL AND MEDIUM ENTERPRISES IN MANADO - Kerap, Stephenny Karen Rahel; Pangemanan, Sifried S.; Tumiwa, Johan . (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Small and Medium Enterprises have significant roles in developing Indonesia?s economy. That is why developing SMEs is crucial to do and developing the whole power of SMEs should start from every single SME in Manado including empowering the core business process of SMEs including in culinary SMEs. In culinary SMEs, providing the food is the most critical aspect to do. This is where the logistic management became crucial as a business activity that supports the Production and Operation Management. Logistic Management key activities considered as the indicators in determining the current logistic management performance and strategies applied by the culinary SMEs to reach the satisfying level of logistic management performance which are the purpose of this research. Using Qualitative research methodology, nine culinary SMEs owner represented each of nine districts in Manado were being interviewed and the result showed that the logistic management performance of culinary SMEs in Manado is in proper condition and the culinary SMEs in Manado also have particular strategies that applied to their businesses and there are total of 10 logistic management strategies that generated from this research.Keywords: logistic management, small and medium enterprises.